Efficiency in dairy units through data envelopment analysis - Herrera, Javier; Barrios, Grisel; Flores, J. O. (Cuban Journal of Agricultural Science, 2013)
Thirty dairy units of the Genetic Cattle Breeding Enterprise ?Valle del Per?? were evaluated from the perspective of relative efficiency through data envelopment analysis. The study was carried in the period 2006-2008. The dairy unit 1, of higher production, and number 23 were the only technically efficient during the three years. In terms of relative efficiency, the enterprise showed a marked irregularity. The overall technical efficiency mean was of 0.69. The pure technical efficiency mean revealed that inefficient dairy units needed to increase their productions by 31 % for reaching the efficient condition. The scale efficiency presented values higher than the remaining indices (0.87). There were higher pure technical efficiency indices in all years, in the dairy units of better productive performance (group I) regarding the dairy units of medium and low production level. The dairy unit 1 was used as reference in 39 opportunities, representing 40 % of the total possible. In 88 % of the cases, the typology of the yield scale was variable. The different efficiency indices estimated (overall, pure technical and of scale) demonstrated that there were difference among the dairy units studied in the evaluated period. Key words: technical efficiency, milk production, indices